Expression quantitative trait locus studies in the era of single-cell omics - Luo, Jie; Wu, Xinyi; Cheng, Yuan; Chen, Guang; Wang, Jian; Song, Xijiao (Frontiers in Genetics, 2023)
Genome-wide association studies (GWAS) have revealed that the regulation of gene expression bridges genetic variants and complex phenotypes. Profiling of bulk transcriptome coupled with linkage analysis (expression quantitative trait locus (eQTL) mapping) has advanced our understanding of the relationship between genetic variants and the gene regulation in the context of complex phenotypes. However, bulk transcriptomics has inherited limitations as the regulation of gene expression tends to be cell-type-specific. The advent of single-cell RNA-seq (scRNA-seq) technology now enables the identification of cell-type-specific regulation of gene expression through single-cell eQTL (sc-eQTL). In this review, we first provide an overview of sc-eQTL studies, including data processing and the mapping procedure of sc-eQTL. We then discuss the benefits and limitations of sc-eQTL analyses. Finally, we present an overview of current and future applications of sc-eQTL discoveries.